2021
DOI: 10.1080/1331677x.2021.1907205
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis using panel data gravity models and scenario forecast simulations for the Romanian exports in the context of COVID-19

Abstract: The paper focuses on the trade performance of Romania, a representative country for the Central and Eastern European region, strongly connected with its European partners in global value chains and thus affected by any change in these countries' relationships with the rest of the world in general and China in particular. Using panel data gravity models for the 2008-2019 period, we find that Romania's exports are significantly influenced by the demand of its major trade partners in the EU, and imports from Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Studies examining the relationship between trade and COVID‐19 focus mainly on GVCs and whether these absorbed or transmitted COVID‐19 shocks. For example, Davidescu et al ( 2022 ) finds that Romania, which is connected with its European partners through GVCs, is affected by changes in partner countries' relationships with the rest of the world. The authors find that Romanian exports are vulnerable to government effectiveness in relation to the other countries, as well as corruption control and cultural values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies examining the relationship between trade and COVID‐19 focus mainly on GVCs and whether these absorbed or transmitted COVID‐19 shocks. For example, Davidescu et al ( 2022 ) finds that Romania, which is connected with its European partners through GVCs, is affected by changes in partner countries' relationships with the rest of the world. The authors find that Romanian exports are vulnerable to government effectiveness in relation to the other countries, as well as corruption control and cultural values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that trade in services declined twice as much as trade in goods and claimed that there is no relationship between the amount of the decline and product complexity. Davidescu et al (2021) constructed a gravity model for Romania's export and claimed that better institutions (e. g. lower corruption, etc.) positively affect country's export and noticed a clustering with the other institutionally similar countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The gravity model was constructed following its theoretical foundations presented by Tinbergen (1962), Anderson (1979), van Wincoop (2003), andAnderson (2011). However, based on the availability of data (international statistic offices still do not provide export data for the full year 2020), and following Davidescu et al (2021), Shahriar et al (2021) and Zainuddin et al (2022), I chose the gravity model of only one exporting country.…”
Section: Model Specificationmentioning
confidence: 99%
“…The COVID-19 pandemic has caused a shock in both demand and supply. A drop in imports from China or the rest of the world has contributed to the reduction of the export flows (Davidescu et al, 2021). A field survey could be undertaken to gather the basic insights and experiences of the main stakeholders who are actively involved in the leather industry of Bangladesh.…”
Section: Conclusion Implications and Future Researchmentioning
confidence: 99%